2001
DOI: 10.1186/1472-6947-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patient preferences for communicating risk estimates: A descriptive pilot study

Abstract: BackgroundPatients increasingly seek more active involvement in health care decisions, but little is known about how to communicate complex risk information to patients. The objective of this study was to elicit patient preferences for the presentation and framing of complex risk information.MethodTo accomplish this, eight focus group discussions and 15 one-on-one interviews were conducted, where women were presented with risk data in a variety of different graphical formats, metrics, and time horizons. Risk d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
112
2
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 30 publications
3
112
2
1
Order By: Relevance
“…22 A study with the objective to elicit patient preferences for the presentation and framing of risk information concluded that patients preferred health risks to be framed in absolute terms and lifetime estimates with a scale of x of 100. 23 The benefits of reporting lifetime risk estimates have also been observed. The widely publicized lifetime risk of breast cancer, estimated to be one in eight (12.6%) for women in the United States, 11 is believed to have contributed to the increase in screening mammogram for early disease detection.…”
Section: Discussionmentioning
confidence: 83%
“…22 A study with the objective to elicit patient preferences for the presentation and framing of risk information concluded that patients preferred health risks to be framed in absolute terms and lifetime estimates with a scale of x of 100. 23 The benefits of reporting lifetime risk estimates have also been observed. The widely publicized lifetime risk of breast cancer, estimated to be one in eight (12.6%) for women in the United States, 11 is believed to have contributed to the increase in screening mammogram for early disease detection.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, one study found that patients preferred their health risks to be presented in absolute terms and that their lifetime estimate of risk be given in an "X in 100" format. 51 In addition, merits of reporting lifetime risk estimates have been observed. For instance, the widely publicized lifetime risk of breast cancer among American women (estimated to be 1 in 8 [12.6%]) 52 is believed to have influenced the increase in screening mammography for early disease detection.…”
Section: Discussionmentioning
confidence: 99%
“…There has been great interest in patients being involved in decision making, and a number of studies have explored patient preferences for presentation and framing of risk information. 3 These have shown that lifetime risk estimates are preferred over 10 or 20 year risk estimates, and absolute risk estimates are preferred over relative risks. 3 There is therefore now a move from using 10-20% risk thresholds towards using lifetime risk, which measures the cumulative risk of developing a disease during the remainder of an individual's life.…”
mentioning
confidence: 99%
“…3 These have shown that lifetime risk estimates are preferred over 10 or 20 year risk estimates, and absolute risk estimates are preferred over relative risks. 3 There is therefore now a move from using 10-20% risk thresholds towards using lifetime risk, which measures the cumulative risk of developing a disease during the remainder of an individual's life. 4 In a linked article published today, Ligthart and colleagues use data from the prospective Rotterdam Study based in the Netherlands (N=10,050; up to 14.7 years follow-up) to alert us to the high burden of absolute lifetime risk at population level of developing pre-diabetes or progressing from pre-diabetes to diabetes and then onto insulin therapy.…”
mentioning
confidence: 99%